2009
DOI: 10.1002/jctb.2241
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient and organic nitrogen‐containing cation‐promoted aerobic oxidation of alkylaromatics in the presence of N‐hydroxyphthalimide

Abstract: BACKGROUD: Direct oxidation of alkylaromatics to the corresponding aromatic ketone is an important process in the manufacture of perfumes, pharmaceuticals, flavors, dyes and agrochemicals. For example, tetralin is oxidized to produce 1-tetralinone, which is a key intermediate in the commercial production of 1-naphthol, 2-hydroxy-1-tetralone, aureolic acid antibiotics and other pharmaceuticals. RESULTS: In this investigation, it was found that alkylaromatics could be efficiently and selectively oxidized to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Cationic initiators. Based on their successfully developed biomimetic catalytic systems, Xu and his coworkers 114 continued to report the promotion effects of methyl violet, methylene blue, and methyl blue (Scheme 4) on the oxidation of tetralin [eqn (20)]. Higher selectivity of 1-tetralinone than that promoted by neutral methyl red was obtained due to their probably favorable decomposition of hydroperoxides.…”
Section: ð18þmentioning
confidence: 99%
“…Cationic initiators. Based on their successfully developed biomimetic catalytic systems, Xu and his coworkers 114 continued to report the promotion effects of methyl violet, methylene blue, and methyl blue (Scheme 4) on the oxidation of tetralin [eqn (20)]. Higher selectivity of 1-tetralinone than that promoted by neutral methyl red was obtained due to their probably favorable decomposition of hydroperoxides.…”
Section: ð18þmentioning
confidence: 99%
“…Data collection: CrysAlis PRO (Agilent, 2012); cell refinement: CrysAlis PRO; data reduction: CrysAlis PRO; program(s) used to solve structure: SHELXS97 (Sheldrick, 2008); program(s) used to refine structure: SHELXL97 (Sheldrick, 2008); molecular graphics: DIAMOND (Brandenburg, 2004); software used to prepare material for publication: publCIF (Westrip, 2010). Aromatic ketone compounds have attracted much attention due to their applications in fragrances and perfume technology (Tong et al, 2009). Studying the relationship between molecular structures and their fragrant properties remains a challenge (Griesbeck et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis of the compound is described by Wang & Huang (2010). For applications of aromatic ketones as fragrances, see: Tong et al (2009). For the relationship between structure and fragrance, see: Griesbeck et al (2012).…”
Section: Related Literaturementioning
confidence: 99%
“…[30][31][32] Nitrogen-cation compounds such as methyl violet could be used as the electron-promoter to combine with NHPI in promoting the metal-free oxidation of aromatic hydrocarbon. 33,34 In nature, it was found that pyridinium cation analogues (e.g. NAD+) played an important role in the redox processes.…”
Section: Introductionmentioning
confidence: 99%